Serum triglyceride level in IUGR babies and its comparison with preterm AGA and term normal babies - Hossain, MA; Islam, MN; Shahidullah, M; Akhter, H (Mymensingh Medical Journal, 2007)
Mymensingh Med J. 2006 Jul;15(2):180-2 The abstract of this article is available on the PubMed website